The complex Tup1‐Cyc8 bridges transcription factor ClrB and putative histone methyltransferase LaeA to activate the expression of cellulolytic genes. Issue 5 (11th February 2022) - Zhang, Xiujun; Hu, Yueyan; Liu, Guodong; Liu, Meng; Li, Zhonghai; Zhao, Jian; Song, Xin; Zhong, Yaohua; Qu, Yinbo; Wang, Lushan; Qin, Yuqi
Abstract: The degradation of lignocellulosic biomass by cellulolytic enzymes is involved in the global carbon cycle. The hydrolysis of lignocellulosic biomass into fermentable sugars is potential as an excellent industrial resource to produce a variety of chemical products. The production of cellulolytic enzymes is regulated mainly at the transcriptional level in filamentous fungi. Transcription factor ClrB and the putative histone methyltransferase LaeA, are both necessary for the expression of cellulolytic genes. However, the mechanism by which transcription factors and methyltransferase coordinately regulate cellulolytic genes is still unknown. Here, we reveal a transcriptional regulatory mechanism involving Penicillium oxalicum transcription factor ClrB (PoClrB), complex Tup1‐Cyc8, and putative histone methyltransferase LaeA (PoLaeA). As the transcription factor, PoClrB binds the targeted promoters of cellulolytic genes, recruits PoTup1‐Cyc8 complex via direct interaction with PoTup1. PoTup1 interacts with PoCyc8 to form the coactivator complex PoTup1‐Cyc8. Then, PoTup1 recruits putative histone methyltransferase PoLaeA to modify the chromatin structure of the upstream region of cellulolytic genes, thereby facilitating the binding of transcription machinery to activating the corresponding cellulolytic gene expression. Our results contribute to a better understanding of complex transcriptional regulation mechanisms of cellulolytic genes and will be valuable for lignocellulosic biorefining. Abstract : This work identified a transcriptional regulatory mechanism of cellulolytic genes involving transcription factors ClrB, Tup1‐Cyc8 complex, and putative histone methyltransferase LaeA in Penicillium oxalicum . We show that the complex Tup1‐Cyc8 bridges TF ClrB and putative histone methyltransferase LaeA to activate the expression of cellulolytic genes. Upon induction conditions, ClrB, binds to the upstream region of cellulolytic genes to recruit the Tup1‐Cyc8 complex. Then, Tup1 interacts with the putative histone methyltransferase LaeA and leads to the opening of the chromatin structure of the upstream region which facilitates the binding of transcription machinery to active the expression of cellulolytic gene.